Requirement of phospholipase C and protein kinase C in cholecystokinin-mediated facilitation of NMDA channel function and anxiety-like behavior - Xiao, Zhaoyang; Jaiswal, Manoj K.; Deng, Pan-Yue; Matsui, Toshimitsu; Shin, Hee-Sup; Porter, James E.; Lei, Saobo (WILEY, 2012)
Although cholecystokinin (CCK) has long been known to exert anxiogenic effects in both animal anxiety models and humans, the underlying cellular and molecular mechanisms are ill-defined. CCK interacts with CCK-1 and CCK-2 receptors resulting in up-regulation of phospholipase C (PLC) and protein kinase C (PKC). However, the roles of PLC and PKC in CCK-mediated anxiogenic effects have not been determined. We have shown previously that CCK facilitates glutamate release in the hippocampus especially at the synapses formed by the perforant path and dentate gyrus granule cells via activations of PLC and PKC. Here we further demonstrated that CCK enhanced NMDA receptor function in dentate gyrus granule cells via activation of PLC and PKC pathway. At the single-channel level, CCK increased NMDA single-channel open probability and mean open time, reduced the mean close time, and had no effects on the conductance of NMDA channels. Because elevation of glutamatergic functions results in anxiety, we explored the roles of PLC and PKC in CCK-induced anxiogenic actions using the Vogel Conflict Test (VCT). Our results from both pharmacological approach and knockout mice demonstrated that microinjection of CCK into the dentate gyrus concentration-dependently increased anxiety-like behavior via activation of PLC and PKC. Our results provide a novel unidentified signaling mechanism whereby CCK increases anxiety. (c) 2011 Wiley Periodicals, Inc.